Capability-Based API Gateway Technology Selection Analysis for Banking Cybersecurity Solution Using AHP Method - Sitorus, Riama Santy; Hutagaol, B Junedi; Simanjuntak, Dita Madonna (Politeknik Ganesha Medan, 2025)
The growing reliance on APIs in the banking sector, driven by digital transformation, necessitates robust API Gateways that balance performance with strong security measures to address risks like API abuse, man-in-the-middle attacks, and data scraping, while ensuring compliance with regulations such as PCI-DSS, GDPR, and OJK standards. This study bridges the gap in technical guidance by developing a comprehensive evaluation framework using the Analytic Hierarchy Process (AHP) to determine the most suitable API Gateway for banking. The findings identify Apigee as the optimal choice, scoring 1.4277 for its superior authentication, traffic encryption, threat detection, deployment flexibility, cloud integration, and API management. IBM API Connect, scoring 0.6186, is a strong alternative with excellent security and management features but limited scalability and deployment flexibility. Kong and Axway API Gateway follow with scores of 0.4215 and 0.4627, excelling in deployment and integration but lacking critical security features for banking. This research emphasizes the strategic importance of selecting the right API Gateway to bolster cybersecurity and API management in banking, recommending Apigee as the primary solution and IBM API Connect for complex IT infrastructures. It also contributes to the literature by providing a structured, quantitative approach to API Gateway selection and suggests future research exploring AI integration, advanced analytics, and cost-benefit analyses for informed decision-making in the financial sector.